Successful wayfinding in age: A scoping review on spatial navigation training in healthy older adults - Fricke, Madeleine; Morawietz, Christina; Wunderlich, Anna; Muehlbauer, Thomas; Jansen, Carl-Philipp; Gramann, Klaus; Wollesen, Bettina (Frontiers in Psychology, 2022)
Introduction: Spatial navigation is a complex cognitive function that declines in older age. Finding one’s way around in familiar and new environments is crucial to live and function independently. However, the current literature illustrates the efficacy of spatial navigation interventions in rehabilitative contexts such as pathological aging and traumatic injury, but an overview of existing training studies for healthy older adults is missing. This scoping review aims to identify current evidence on existing spatial navigation interventions in healthy older adults and analyze their efficacy. Methods: To identify spatial navigation interventions and assessments and investigate their effectiveness, four electronic databases were searched (Pubmed, Web of Science, CINAHL and EMBASE). Two independent reviewers conducted a screening of title, abstract and full-texts and performed a quality assessment (following Kmet et al., 2004). Studies were eligible if (1) published in English, (2) the full text was accessible, (3) at least one group of healthy older adults was included with (4) mean age of 65 years or older, (5) three or more spatial navigation-related training sessions were conducted and (6) at least one spatial ability outcome was reported. Results: Ten studies were included (N = 1,003, age-range 20-95 years, 51.5% female), only healthy older adults (n = 368, mean age ≤ 65) were assessed further. Studies differed in sample size (n = 22-401), type of training, total intervention duration (100 minutes-50 hours), and intervention period (1-16 weeks). Conclusions: The spatial navigation abilities addressed and the measures applied to elicit intervention effects varied in quantity and methodology. Significant improvements were found for at least one spatial ability-related outcome in six of ten interventions. Two interventions achieved a non-significant positive trend, another revealed no measurable post-training improvement, and one study did not report pre-post-differences. The results indicate that different types of spatial navigation interventions improve components of spatial abilities in healthy older adults. The existing body of research does not allow conclusions on transferability of the trained components on everyday life spatial navigation performance. Future research should focus on reproducing and extending the promising approaches of available evidence. From this, valuable insights on healthy aging could emerge.